Authoritarian Parenting and Emotion Regulation in Late Adolescence - Windy Frianti Darwis; Christiana Hari Soetjiningsih; Arthur Huwae (Green Publisher Indonesia, 2025)
Adolescence is a development stage that is emotionally vulnerable, and parenting plays a crucial role in shaping a child's ability to manage emotions. This study aims to examine the relationship between authoritarian parenting and emotion regulation in late adolescents. A quantitative approach with a correlational design was employed. The participants consisted of 350 late adolescents aged 18–22 years, selected using accidental sampling. The instruments used were the Parental Authority Questionnaire (PAQ) to measure authoritarian parenting and the Emotion Regulation Questionnaire (ERQ) to assess emotion regulation. The results revealed a significant negative correlation between fathers' authoritarian parenting and emotion regulation (r = -0.226; p < 0.01), as well as between mothers' authoritarian parenting and emotion regulation (r = -0.254; p < 0.01). These findings indicate that the higher the level of authoritarian parenting received by adolescents, the lower their ability to regulate emotions adaptively. This highlights the importance of supportive and open parenting in fostering adolescents' emotional development.